Effect of a peptide in cosmetic formulations for hair volume control - Cruz, Célia F. (2017)
Objective The capacity of hair to absorb water causes changes in its physical and cosmetic properties under different environmental conditions. Hence, the control of hair volume in variable relative humidity settings is an important topic in cosmetics. The behaviour of two types of hair, Caucasian and Asian, was studied regarding their volume change in different relative humidity conditions. The ability of a peptide as a hair volume treatment was evaluated in two climate control formulations. Methods Tresses of the two types of hair were tested in two relative humidity (RH) conditions: (A) variable relative humidity (2 hours 40% RH, followed by 2 hours 90% RH and 2 hours of 40% RH), and (B) continuous high relative humidity (90% RH for 6 hours). Changes in the hair tress volume were assessed throughout time. Hair treated with two climate control formulations, with and without a peptide (KP peptide), were tested under the two relative humidity conditions. Results Caucasian hair had a higher change in volume compared to the Asian hair in variable and high relative humidity conditions. The hair volume increase when subject to high air humidity, and it was lower with the incorporation of a peptide into climate control formulations. Conclusion Caucasian hair showed higher volume than Asian hair when submitted to both relative humidity conditions. The incorporation of the peptide into the climate control formulations, a base (mostly composed of water 94%) and an ethanolic, was found to reduce the volume of Caucasian hair tresses. The presence of the peptide improved the hair volume change more than 60% in high relative humidity conditions.